The Kathmandu Declaration on Global CVD/Hypertension Research and Implementation Science: A Framework to Advance Implementation Research for Cardiovascular and Other Noncommunicable Diseases in Low- and Middle-Income Countries - Aifah, Angela (2019)
Highlights NCD represent a serious challenge globally, particularly in LMIC.Implementation research capacity building are critical to inform the prevention and control of NCD in LMIC.Sustainable evidence-based strategies can reduce mortality and prevent avoidable illness from NCD.Strategic change agents (i.e., key stakeholders, institutions, communities, health systems, patients, and families) should work collaboratively to make the necessary advancements to reducing the burden of NCD in LMIC.